The 2010 Mw 7.8 Mentawai earthquake : very shallow source of a rare tsunami earthquake determined from tsunami field survey and near-field GPS data - Huang, Zhenhua (2012)
The Mw 7.8 October 2010 Mentawai, Indonesia, earthquake was a “tsunami earthquake,”